COMMIPHORA MUKUL EXTRACT AND GUGGULSTERONE EXHIBIT ANTITUMOUR ACTIVITY THROUGH INHIBITION OF CYCLIN D1, NF-Κß AND INDUCTION OF APOPTOSIS IN ORAL CANCER CELLS - Bharti, Vijaya; Gupta, Umesh D; Das, Satya N (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Comiphora mukul, a promising medicinal plant and its constituent Guggulsterone (GS) is used in Ayurveda since decades. This study was aimed to investigate the anticancer potential of C. mukul and GS on oral cancer cell lines (SCC-4, KB). MTT assay was used to determine tumour cell proliferation, propidium iodide labeling and annexin V- binding, followed by flow cytometry was used to determine cell cycle and apoptosis of tumor cells after treatment. Expression of regulatory proteins such as NF-κß, cyclin D1, p53 and vascular endothelial growth factor was determined by western blot. C. mukul and GS significantly inhibited tumor cell growth, caused cell cycle arrest and apoptosis in both tumor cells. Such activities appeared to be due to inhibition of NF-κß, cyclin D1and restoration of p53. Overall our data suggests that C. mukul and GS may be developed as chemopreventive and chemotherapeutic drug for oral cancer. Keywords: Commiphora mukul, Oral cancer, Antitumor, Cell cycle, Apoptosis, NF-κß, Cyclin D1, P53.